To find the 9th term of the arithmetic sequence using the explicit formula \( A^n = \frac{1}{4} + (n-1) \cdot \frac{1}{2} \), we need to substitute \( n = 9 \) into the formula.
-
Substitute \( n = 9 \):
\[ A^9 = \frac{1}{4} + (9-1) \cdot \frac{1}{2} \]
-
Calculate \( (9-1) \):
\[ (9-1) = 8 \]
-
Now substitute that value into the formula:
\[ A^9 = \frac{1}{4} + 8 \cdot \frac{1}{2} \]
-
Calculate \( 8 \cdot \frac{1}{2} \):
\[ 8 \cdot \frac{1}{2} = 4 \]
-
Now add it to \( \frac{1}{4} \):
\[ A^9 = \frac{1}{4} + 4 = \frac{1}{4} + \frac{16}{4} = \frac{17}{4} \]
-
To convert \( \frac{17}{4} \) into a mixed number:
\[ \frac{17}{4} = 4 \frac{1}{4} \]
So, the 9th term \( A^9 \) is \( 4 \frac{1}{4} \).
Therefore, the correct response is:
4 1/4